Emergency department interventions for frailty (EDIFY): improving functional outcomes in older persons at the emergency department through a multicomponent frailty intervention. (2nd February 2022) - Chong, Edward; Zhu, Birong; Ng, Sheryl Hui Xian; Tan, Hongyun; Goh, Eileen Fabia; Molina, Joseph De Castro; Pereira, Michelle Jessica; Kaur, Palvinder; Baldevarona-Llego, Jewel; Chia, Jia Qian; Chong, Amanda; Cheong, Selina; et al.
Abstract: Objectives: emergency department interventions for frailty (EDIFY) delivers frailty-centric interventions at the emergency department (ED). We evaluated the effectiveness of a multicomponent frailty intervention (MFI) in improving functional outcomes among older persons. Design: a quasi-experimental study. Setting: a 30-bed ED observation unit within a 1, 700-bed acute tertiary hospital. Participants: patients aged ≥65 years, categorised as Clinical Frailty Scale 4–6, and planned for discharge from the unit. Methods: we compared patients receiving the MFI versus usual-care. Data on demographics, function, frailty, sarcopenia, comorbidities and medications were gathered. Our primary outcome was functional status—Modified Barthel Index (MBI) and Lawton's iADL. Secondary outcomes include hospitalisation, ED re-attendance, mortality, frailty, sarcopenia, polypharmacy and falls. Follow-up assessments were at 3, 6 and 12 months. Results: we recruited 140 participants (mean age 79.7 ± 7.6 years; 47% frail and 73.6% completed the study). Baseline characteristics between groups were comparable (each n  = 70). For the intervention group, MBI scores were significantly higher at 6 months (mean: 94.5 ± 11.2 versus 88.5 ± 19.5, P  = 0.04), whereas Lawton's iADL scores experienced less decline (change-in-score: 0.0 ± 1.7 versus −1.1 ± 1.8, P  = 0.001). Model-based analyses revealed greater odds of maintaining/improving MBI in the intervention group at 6 months [odds ratio (OR) 2.51, 95% confidence interval (CI) 1.04–6.03, P  = 0.04] and 12 months (OR 2.98, 95% CI 1.18–7.54, P  = 0.02). This was similar for Lawton's iADL at 12 months (OR 4.01, 95% CI 1.70–9.48, P  = 0.002). ED re-attendances (rate ratio 0.35, 95% CI 0.13–0.90, P  = 0.03) and progression to sarcopenia (OR 0.19, 95% CI 0.04–0.94, P  = 0.04) were also lower at 6 months. Conclusions: the MFI delivered to older persons at the ED can possibly improve functional outcomes and reduce ED re-attendances while attenuating sarcopenia progression.